Community - Florian Sichling (Social Work and Society, 2008)
The term community in the English language can be traced back to the 14th century and originates from the French word comunetÃ© and the Latin word communitatem. In English the term initially came to denote five distinct senses. Community served as a distinction of the common people from those of rank (1), as a denotation of a state or organized society (2), the people of a district (3), as a designation for the community of shared interests (4) and as a sense of common identity and characteristics (5). In these early meanings of the term it is important to note the distinction between the designation of actual social groups on the one hand and the indication of a particular relational quality on the other.